TRANSFORMATIONAL LEADERSHIP, PERSON-ORGANIZATION FIT AND ALTRUISM BEHAVIOR RELATIONSHIP: THE MEDIATOR EFFECT OF PERSON-ORGANIZATION FIT (Third Sector Social Economic Review, 2020)
The aim of this research is to reveal relationships among variables such as transformational leadership, person-organization fit and altruism behavior. With that aim data were obtained by survey from 440 participators who work in a central department of a ministry in December 2019 and these data were analyzed by SPSS 26 package program. First of all, in that study validity and reliability analyses are done. Correlation and regression analyses are done both to reveal the relationships among related dependent and independent variables and to test hypotheses. Both Baron and Kenny and Hayes mediation models are used to show mediation effect. According to findings, it is determined whether the perceptions of employees about transformational leadership increase, also levels of person-organization fit and altruism behavior increase too. It is found that whether levels of person-organization fit increase, also altruism levels of extra-role behaviors increase too. Lastly, person-organization fit has no mediation effect through transformational leadership’s effect on altruism behavior.
Keywords: Transformational Leadership; Person-Organization Fit; Altruism Behavior